Limits of Autonomy Principle in Documentary Letters of Credit; Perspective of English Law - ALAVI, Hamed (Journal of Legal Studies, 2017)
In this article, the author reviews the approach of English courts to limits of autonomy principle and tries to answer the following research questions: What obligations should the applicant fulfil while opening a credit in accordance with the underlying contract? What are the sellerâ€˜s remedies when the buyer fails to perform his duties regarding opining and performance of the credit? On the other hand, what are the sellerâ€˜s duties in the process of opening the credit and what will be the buyerâ€˜s remedy in case of his failure? What is the legal position regarding variation of the credit? What is the position of court regarding absolute or conditional nature of the credit? In order to answer the above research questions, paper is divided into seven parts: after the introductory comments, the second part will review the nature of the buyerâ€˜s obligation in opening the credit. The third part is focused on effect of non-compliance by the buyer and the fourth part studies the variation of the credit and its effect on partyâ€˜s rights within the underlying contract. Part five deals with the buyer’s rights after opening the credit while part six will discuss the absolute or conditional nature of the payment obligation to pay under the LC. Last but not the least, the final part will provide some concluding remarks.